Penerapan Model Student Facilitator and Explaining (SFE) dengan Media Poster untuk Meningkatkan Kemampuan Representasi Matematis Siswa - Sari, Sonia Andam; Nasution, Eline Yanty Putri; Laswadi, Laswadi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
This study used quantitative approach with experiment method. The research design was posttest-only control group. The purpose of this study was to investigate the effect of cooperative learning model type Student Facilitator and Eksplaining (SFE) with poster media through students’ mathematical representation ability. The population was all of seventh grade students in SMPN 7 Sungai Penuh. Two sample were choosen withdraw. Conventional method was implemented in control group, while cooperative learning model type Student Facilitator and Eksplaining (SFE) with poster media was implemented in experiment group. The instrument in this study was students’ mathematical representation ability test that the test items was analyzed first. The instrument was given in the end of learning process in both groups. The result of the data analysis was obtained that: (1) the average of students’ mathematical representation ability test in control group was 66,67 while in experiment group was 73,43; (2) the students’ mathematical representation ability who study under cooperative learning model type Student Facilitator and Eksplaining (SFE) with poster media was higher than who study under conventional method; (3) there was an effect of cooperative learning model type Student Facilitator and Eksplaining (SFE) with poster media through the students’ mathematical representation ability.